FEASIBILITY STUDY FOR BUSINESS DEVELOPMENT OF SOMIPREK CHICKEN AND STEAK RESTAURANT - Budiono, Puguh; Sutanto, J.E (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the feasibility of expanding Somiprek Chicken & Steak by examining market and marketing aspects, legal compliance, technical and operational elements, human resource management, financial viability, and environmental considerations. A quasi-qualitative approach was adopted, employing triangulation methods including interviews, observations, and document analysis. Data was collected from various sources, such as owners, employees, and relevant experts. The results indicate that Somiprek Restaurant has significant market potential in Surabaya with a strategic market segment and promising growth prospects. On the technical aspect, the proposed location is strategically positioned, with infrastructure and layout supporting operational efficiency. From a management perspective, the organizational structure has been designed to support business expansion, including recruitment strategies, training, and competitive compensation plans. Financial analysis revealed positive outcomes, with Payback Period, NPV, IRR, and ROI values indicating investment feasibility. Additionally, Somiprek Restaurant has complied with environmental standards through adherence to SPPL regulations for restaurant operations. In conclusion, the business expansion of Somiprek Restaurant to Surabaya is deemed feasible. Strategic recommendations are provided to optimize market potential, operational efficiency, and business sustainability.